Management of Fistulas in Patients with Crohn'S Disease: Antibiotic to Antibody - Pierre Paré (Canadian Journal of Gastroenterology)
Fistulas are common in patients with Crohn's disease and, when associated with inflammatory disease and established for several weeks, tend to be chronic. Perianal fistulas are the most frequent complication of, and are most often associated with, colonic disease. Perianal fistulas commonly require surgical resection and permanent ileostomy. Antibiotics, cyclosporine, methotrexate and thalidomide have been used in uncontrolled trials; only azathioprine, 6-mercaptopurine and infliximab have been assessed in double-blind, placebo controlled studies. Relapse of the fistula occurs with all drugs, unless treatment is continued long term. Each drug differs in its onset of action and long term tolerability. An approach to fistulizing disease in Crohn's disease is suggested.